Liver Transplantation Using Allografts With Recent Liver Blunt Trauma: A Nationwide Audit From the French CRISTAL Biomedicine Agency Registry. Issue 3 (22nd November 2022) - Seckler, Florian; Turco, Célia; Mohkam, Kayvan; Addeo, Pietro; Robin, Fabien; Cauchy, François; Maulat, Charlotte; Brustia, Raffaele; Paquette, Brice; Faitot, François; Weil Verhoeven, Delphine; Minello, Anne; et al.
Abstract : Background: In the current setting of organ shortage, brain-dead liver donors with recent liver trauma (RLT) represent a potential pool of donors. Yet, data on feasibility and safety of liver transplantation (LT) using grafts with RLT are lacking. Methods: All liver grafts from brain-dead donors with RLT proposed for LT between 2010 and 2018 were identified from the nationwide CRISTAL registry of the Biomedicine Agency. The current study aimed at evaluating 1-y survival as the primary endpoint. Results: Among 11 073 LTs, 142 LTs (1.3%) using grafts with RLT were performed. These 142 LTs, including 23 split LTs, were performed from 131 donors (46.1%) of 284 donors with RLT proposed for LT. Transplanted grafts were procured from donors with lower liver enzymes levels ( P < 0.001) and less advanced liver trauma according to the American Association for the Surgery of Trauma liver grading system ( P < 0.001) compared with not transplanted grafts. Before allocation procedures, 20 (7%) of 284 donors underwent damage control intervention. During transplantation, specific liver trauma management was needed in 19 patients (13%), consisting of local hemostatic control (n = 15), partial hepatic resection on back-table (n = 3), or perihepatic packing (n = 1). Ninety-day mortality and severe morbidity rates were 8.5% (n = 12) and 29.5% (n = 42), respectively. One-year overall and graft survival rates were 85% and 81%, and corresponding 5-y rates were 77% and 72%, respectively. Conclusions: Using liver grafts from donors with RLT seems safe with acceptable long-term outcomes. All brain-dead patients with multiorgan trauma, including liver injury, should be considered for organ allocation.